Ecologia alimentar de aves insetívoras de um fragmento de mata decídua do extremo norte da Mata Atlântica - Souto, Glauber Henrique Borges de Oliveira (2010)
The diet study of birds has contributed historically as a model for use to understanding ecological patterns and strategies used by several other groups of vertebrates, which are observed in season patterns and temporal availability of resources, and other. This study has as objective generate information concerning the diet of insectivorous birds during rainy season and dry season, as well as analyze Index food importance, niche overlap, niche breadth, electivity, and seasonal availability of prey. The study was conducted in a fragment of about 270 ha (center coordinates and 5 º 53'S 35 ° 23'W). The sampling of birds occurred between March 2008 and December 2009 in three pre-established trails. Catches of birds were performed using 10 mist nets placed in line, where each trails was sampled once a month. Samples of pellets were obtained by means of tartar emetic. Sampling of availability of prey occurred between February 2009 to December 2009. We used two methods of sampling (pitfall traps and Shake cloths). We captured 269 individuals of 21 species of insectivorous birds. We collected 4116 invertebrates of which 3259 in the rainy season and 857 in the dry season. We obtained 174 samples stomach, where 10 species were exclusively insectivorous diet, nine fed on insect/plant material, an insect/plant material/vertebrate and one for insect/vertebrate. During the rainy season was observing difference between the consumption of items with higher food importance. The Coleoptera was item with higher food importance (73%), followed by Formicidae (7%) and Araneae (6%). During the dry season, no difference was found difference between the consumption of items with higher food importance. The Coleoptera was item with higher food importance (34%), followed by seeds (29%) and Formicidae (18%). The highest levels of niche overlap occurred during the rainy season, while the dry season was characterized by high levels of niche 11 segregation. This indicates that the local insectivorous birds community was structured differently between periods. No was found correlation between the values of niche breadth to the mean weight of the body size. We observed seasonal patterns in prey availability, with the peak availability of invertebrates observed seasonal patterns in rainy season. The insectivorous birds selected the same species richness during both periods, showing a specialized diet. Thamnophilus pelzelni was the only species that had their diet influenced by seasonality. Regarding the overall diet of insectivorous birds, observed a high consumption of prey, whose food availability caused the birds could invest and increase their food resources